'Now we're talking!' Scripting masculinity and emotionality in everyday life. (6th May 2010) - Arfanis, Konstantinos; Lewis, Charlie
Traditional analyses have tended to emphasise the negative role that masculinity stereotypes play in the lives of modern men, and how women, in turn, misunderstand men. In this paper, the issue of masculinity is explored through the narratives of men at work, examining how this issue is understood and acted out in the everyday lives of modern men. The findings indicated that men are aware of the tension between the unitary stereotype of male detachment and the complex ways in which men develop and manage their self-presentations. Throughout the study an abundance of strategies were implemented for managing their emotionality, and we use the term 'scripting' to define how such strategies are implemented. We suggest that the abundance of scripting in our interviews suggests a need to take a closer look at masculinity and its relation to emotionality.